Combination Methods for Screening Marine Actinomycetes Producing Potential Compounds as Anticancer - Yuyun Farida; Jaka Widada; Edy Meiyanto (Indonesian Journal of Biotechnology, 2007)
Marine actinomycetes is a robust source of secondary metabolites including anticancer compounds . The objective of this research was to select marine actinomycetes producing potential compounds as anticancer used combination methods that consist of amplification PKS I (polyketide synthases type I) and NRPS (non ribosomal peptide synthetases) genes, analysis the diversity of secondary metabolites and genetic. Selected isolates were used for cytotoxicity assay. PKS I and NRPS genes were amplified using sets of degenerate primers. K1F and M6R were used for amplify ketosynthase and methyl-malonyl-CoA transferase modules of PKS I gene which targeted sequences 1200-1400 bp. A3F and A7R were used for amplify adenilation domains of NRPS gene which targeted sequences 700-800 bp. The diversity of secondary metabolites was analized by TLC and densitometry of ethyl acetate extracts. Genetic diversity was analized by repetitive DNA fingerprinting using BOXA1R primers. The cytotoxicity of secondary metabolites on T47D and MCF7 breast cell lines cancer was measured by MTT assay method. Fifty two marine actinomycetes isolates were screened using combination methods. Ten isolates were detected encoding both PKS I and NRPS genes, whereas 11 isolates were detected encoding the NRPS gene. The screening by analysis of secondary metabolites and genetic diversity methods were obtained 6 selected isolates for cytotoxicity assay, which consist of 3 isolates encoding both PKS I and NRPS genes and 3 isolates encoding NRPS gene.Isolate 1 had high cytotoxicity with the IC50 on T47D cell was 19 μg/ml and the IC50 on MCF7 cell was 7 g/ml. This findings suggests that combination methods were effective and efficient way to select marine actinomycetes producing potential compounds as anticancer.